Pengaruh Pemberian Edukasi Video Periksa Payudara Sendiri (SADARI) terhadap Pengetahuan dan Sikap Mahasiswi dalam Pencegahan Kanker Payudara - Sri Hastuti, Ni Komang; Astuti, Ika Widi; Sanjiwani, Ida Arimurti (Jurnal Gema Keperawatan, 2024)
Breast cancer is the most commonly diagnosed cancer in women and is the second leading cause of death from cancer in women in the world. Breast Self Examination (BSE) is the cheapest, easiest and simplest way that can be done by every individual to detect signs and symptoms of breast cancer. The purpose of this study was to determine the effect of providing BSE video education on knowledge and attitudes in preventing breast cancer in female students at Udayana University. This study used a pre-experimental quantitative method with a one group pre-test post-test design. The respondents in this study were 95 students spread across seven study programs at the Faculty of Engineering Udayana University. The sampling technique used in this study was probability sampling using stratified random sampling. The measuring instrument in this study used a questionnaire of knowledge and attitude towards BSE. Data analysis in this study used the Wilcoxon test and McNemar. The Wilxocon Test results on the knowledge variable showed a significant difference between before and after being given education about breast cancer prevention and SADARI (p = 0,000). Then the results of McNemar on the attitude variable showed a significant difference between before and after being given education (p = 0,001). Therefore it can be concluded that the provision of interventions in the form of education on breast cancer prevention and BSE with video has an effect on increasing knowledge and attitudes in students of the Faculty of Engineering, Udayana University. This study is expected to be used as a reference to develop the provision of health promotion using video in early detection of breast cancer so that the hope is to reduce the incidence of breast cancer.